2016
DOI: 10.1016/j.actamat.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orientation and lamellar spacing of Fe2B on interfaces and corrosion behavior of Fe-B alloy in hot-dip galvanization

Abstract: a b s t r a c t The effects of orientation and lamellar spacing on the interface microstructure and corrosion behavior of a directionally solidified (DS) Fe-B alloy in a hot-dip galvanization bath were investigated. The results indicated that the microstructure of the DS Fe-B alloy consisted of oriented a-Fe and Fe 2 B grains. The oriented Fe 2 B with [002] preferred growth orientation displayed low-angle grain boundaries on the Fe 2 B (001) basal plane. The DS Fe-B alloy with Fe 2 B vertical to the corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…(2) The addition of Ti promoted the formation of the dispersed TiB 2 and TiC phases which consumed some amount of [B] and [C].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The addition of Ti promoted the formation of the dispersed TiB 2 and TiC phases which consumed some amount of [B] and [C].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The Fe 2 B phase has been shown to be responsible for the superior wear resistance and mechanical properties of these alloys. 5,6) These alloys have been widely used to prepare Fe-B-C overlays on substrates for enhancement of the wear resistance using conventional hard facing techniques, such as the laser cladding, 7) plasma transferred arc welding, 8) and arc welding.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations revealed the erosion-corrosion interaction of Fe-B alloy in flowing zinc by Al-inhibition addition, and results indicated that pure corrosion and erosion simultaneously affected the total material loss rate [19,20]. The static corrosion of Fe-B alloy in liquid zinc indicated that a well-adhered interfacial film could gain by controlling the orientation and lamellar spacing of Fe2B to produce a pinning effect at the orientation interface [21,22]. Moreover, the liquid zinc temperature and Fe2B morphologies (netlike and columnar Fe2B) manifested that the corrosion dominates the product dissolution, while flow erosion governs the Fe2B spalling in flowing liquid zinc, which may depend on the interfacial pinning effect [23,24].…”
Section: Background and Experimentalmentioning
confidence: 95%
“…(Figure 5c). However, α-Fe grains in [110] orientation are maintained adjacent to the Fe2B [21], which probably reveals it possesses better corrosion resistance to flowing zinc. Moreover, no selective and preferential erosion-corrosion path occurs on α-Fe/Fe2B phase boundary, and α-Fe still displays uniform dissolution in flowing zinc (Figure 5d).…”
Section: Effects Of Erosion Time and Fe2b Lamellar Spacing On Erosionmentioning
confidence: 99%
“…Though, it has been observed that problem of contamination at matrixreinforcement interfaces the powder metallurgy route [9][10][11], to synthesize Tic reinforced in aluminum matrix, the in-situ approach is much economical and suitable. Through in-situ approach method of chemical reaction, many of the researchers have synthesized Tic particulates to form a very fine thermodynamically stable ceramic phase using Al-Ti-C system [12][13][14][15][16]. In aluminum alloy the Tic particulates synthesis the chemical reaction of graphite powders and K 2 TiF 6 .…”
Section: Introductionmentioning
confidence: 99%